Juridical Review Of Cybercrime In The Criminal Act Of Defamation According To Ite Law And Criminal Law - Abdurrahman Harits Ketaren (International Journal of Society and Law, 2024)
The development of the internet is indeed extraordinary. The rapid development of internet technology has caused new crimes to emerge, such as data manipulation, espionage, sabotage, provocation, money lounding, hacking, software theft, and hardware destruction, defamation, cyberbullying, and various others. Based on the Laws and Regulations, it is known that the elements of the crime of defamation are found in the Criminal Code, namely in Article 310 and Article 27 paragraph 3 of Law Number 8 of 2011 concerning Electronic Information and Transactions. Regulations regarding the offense of defamation can be found in the Criminal Code article 310 and Laws outside the Criminal Code, namely Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) article 27 paragraph 3 before the existence of the Electronic Transaction and Information Law No. 8 of 2011 there was a legal vacuum in which the criminal act of defamation was only regulated in the Criminal Code because of this vacuum, the Electronic Transaction Information Law was formed in order to create legal certainty when defamation was carried out in electronic media.